Pengembangan Sistem Informasi KIM (Kelompok Informasi Masyarakat) KOMINFO Jatim Berbasis Web - Mohammad Mirza Zanuar; Mochamad Chandra Saputra; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of programs that being held by KOMINFO JATIM is ‘Kelompok Informasi Masyarakat' that have a purpose to increase the public participation to contribute for sharing an information on their region. Based on observation and interview , KIM program has not been able to run well becasuse of some problems. The absence of control mechanism in the KIM program, such as controlling the incoming article and controlling the registered kim members. The previous alternative controls are done manually which creates new problems that are poor data management. Base on these problem, KIM information system are being developed to serve as a medium for the implementation of the KIM program. Development method used is waterfall method. The Naive Bayes method is used to classify unexpected articles (spam). Then used the feature of laravel that is middleware to manage role available in KIM information system. In testing, basic path tests, validation testing, compatibility tests, and user acceptance tests were performed. For classificatoin feature, test is done by using coincidence matrix table to get the value from precision,recall, and accuracy.